Micellaneous materials, Protestant missionaries to the American Indians, 1787 to 1862 - Berkhofer, Robert F. (1960)
In this doctoral dissertation (Cornell University, 1960), Berkhofer compares and contrasts the differing missionary activities of Quakers, Moravians, Congregationalists, Presbyterians, Baptists, and Methodists, to reactions among the Oneida, Seneca, Cherokee, Choctaw, Ojibwa [Ojibwe], Sioux [Dakota], Ottawa [Odawa], and Nez Perce.